Human-Robot Interaction Theory and Application - Anbarjafari, Gholamreza; Escalera, Sergio (IntechOpen, 2018)
This book takes the vocal and visual modalities and human-robot interaction applications into account by considering three main aspects, namely, social and affective robotics, robot navigation, and risk event recognition. This book can be a very good starting point for the scientists who are about to start their research work in the field of human-robot interaction.